HAPPINESS AT WORK, WORK LIFE BALANCE, AND JOB SATISFACTION TERHADAP KINERJA KARYAWAN BAYANG CAFE JIMBARAN - Wijaya, Gede Crisna (Jurnal Riset Entrepreneurship, 2024)
This study aims to explore the role of happiness at work, work life balance, and job satisfaction on the performance of employees of Bayang Café Jimbaran. The target population used is all employees who work at Shadow Café Jimbaran. Through the saturated sampling method, 36 participating employees became respondents. Empirical data were collected through the distribution of online questionnaires using Google Form and then analyzed through the Structural Equation Modeling (SEM) approach with Partial Least Square (PLS). The findings in the study show that employee happiness at work and balance of work time with personal life will be able to increase job satisfaction. Furthermore, the results of the study confirm that a high level of job satisfaction will have an impact on an increasingly optimal employee performance. An interesting finding in this study is the finding of a significant role for job satisfaction as a mediating variable. This research is able to contribute positively to the HR management literature and can provide practical implications for the management of Bayang Café Jimbaran to always increase happiness, satisfaction, and always provide support for its employees.